COPs and POPs Patrol Inflammasome Activation. Issue 2 (19th January 2018) - Indramohan, Mohanalaxmi; Stehlik, Christian; Dorfleutner, Andrea
Abstract: Sensing and responding to pathogens and tissue damage is a core mechanism of innate immune host defense, and inflammasomes represent a central cytosolic pattern recognition receptor pathway leading to the generation of the pro-inflammatory cytokines interleukin-1β and interleukin-18 and pyroptotic cell death that causes the subsequent release of danger signals to propagate and perpetuate inflammatory responses. While inflammasome activation is essential for host defense, deregulated inflammasome responses and excessive release of inflammatory cytokines and danger signals are linked to an increasing spectrum of inflammatory diseases. In this review, we will discuss recent developments in elucidating the role of PYRIN domain-only proteins (POPs) and the related CARD-only proteins (COPs) in regulating inflammasome responses and their impact on inflammatory disease. Graphical abstract: Highlights: POPs and COPs function as inflammasome inhibitors. POPs and COPs are encoded in humans, but are lacking in mice. POPs are inhibitors that competitively bind to PYD-containing inflammasome proteins. COPs are inhibitors that competitively bind to CARD-containing inflammasome proteins.